An Efficient Strategy for Boosting Photogenerated Charge Separation by Using Porphyrins as Interfacial Charge Mediators. Issue 47 (11th October 2019) - Ning, Xingming; Lu, Bingzhang; Zhang, Zhen; Du, Peiyao; Ren, Hongxia; Shan, Duoliang; Chen, Jing; Gao, Yunjing; Lu, Xiaoquan
Abstract: Surface recombination at the photoanode/electrolyte junction seriously impedes photoelectrochemical (PEC) performance. Through coating of photoanodes with oxygen evolution catalysts, the photocurrent can be enhanced; however, current systems for water splitting still suffer from high recombination. We describe herein a novel charge transfer system designed with BiVO4 as a prototype. In this system, porphyrins act as an interfacial‐charge‐transfer mediator, like a volleyball setter, to efficiently suppress surface recombination through higher hole‐transfer kinetics rather than as a traditional photosensitizer. Furthermore, we found that the introduction of a "setter" can ensure a long lifetime of charge carriers at the photoanode/electrolyte interface. This simple interface charge‐modulation system exhibits increased photocurrent density from 0.68 to 4.75 mA cm −2 and provides a promising design strategy for efficient photogenerated charge separation to improve PEC performance. Abstract : A whole new ball game : Porphyrins were found to act as an interfacial‐charge‐transfer mediator, like a "volleyball setter", to efficiently suppress surface charge recombination owing to higher hole‐transfer kinetics rather than as a traditional photosensitizer (see picture). The introduction of a "setter" ensured that charge carriers had a long lifetime at the photoanode/electrolyte interface and led to increased photocurrent density.